Do psychological barriers exist in Latin American stock markets? - Júlio Lobão (2020)
We examine for the first time the major stock markets of eight Latin American countries for indication of psychological barriers at round numbers. We test for uniformity in the trailing digits of the indices and use regression and GARCH analysis to assess the differential impact of being above or below a possible barrier. The Chilean stock market seems to be significantly different from its counterparts as it is the only one that showed virtually no signs of psychological barriers. There is mild to strong evidence of barriers in the remaining markets. These findings challenge the notion that most Latin American markets are unpredictable and lend credit to the claim that technical analysis strategies can be useful in some of these markets.